EHF-therapy in complex treatment of psorias - V. S. Dmitruk (Бюллетень сибирской медицины, 2005)
The purpose of the study – elaborating the complex immuno – correcting method for psoriasis patients, treatment in growing progressively worse phase using EHF (extreme high frequency) radiation.103 persons with diagnosis progressing psoriasis were investigated. All patients divided into two groups. The first consisted of 73 persons treated with EHF therapy with apparatus «Stella-2» in combination with traditional therapy. The second group consisted of 30 persons treated traditionally (vitamins, calcium preparations, biostimulators, indifferent and reducing liniments).Immune status research consisted in determination of: main classes of immunoglobulins (IgA, IgM, IgG) according to Manchini, level of circulating immune complex (CIC) using the method of selective precipitation in 3% glycol, subpopulations of lymphocytes, caring CD3, CD4, CD8, CD16, CD72 by immunofluorescent method, phagocytes activity of neutrophiles was investigated by testing with absorption of nitroblue tetrazole (NBT-test).It was determined as a result of experiments, that EHF radiations (frequency range 4,7–5,1 mm) have a wholesome effect on immune system of psoriasis patients in progressing phase (quantitative increasing of T-lymphocytes CD3, quantitative decreasing of CIC, intensification of neutrophiles granulocyte metabolic activity).Common individual effect of EHF radiations (frequency range 4,7–5,1 mm) in combination with traditional therapy for treating psoriasis patients has the decreasing influence on durations of progressing psoriasis phase up to 5–7 days and quantitative diminution of early relapses up to 23,3%.